2004
DOI: 10.1002/pola.20054
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphiphilic network polymers consisting of nonpolar, short primary polymer chains and polar, long crosslink units: Influence of characteristic dangling chains on swelling behavior of resulting amphiphilic gels

Abstract: Novel amphiphilic network polymers consisting of nonpolar, short primary polymer chains and polar, long crosslink units were prepared, and the swelling behavior of resulting amphiphilic gels is discussed by focusing on the influence of characteristic dangling chains; that is, benzyl methacrylate (BzMA) was copolymerized with tricosaethylene glycol dimethacrylate [CH2C(CH3)CO(OCH2CH2)23OCOC(CH3)CH2, PEGDMA‐23] in the presence of lauryl mercaptan as a chain‐transfer agent because BzMA forms nonpolar, short pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…[22] This ideal NPP formation was developed to the preparation of novel amphiphilic polymers [11] and, moreover, amphiphilic CSMs. [37][38][39] As the latter case of controlling intramolecular crosslinking in the free-radical crosslinking monovinyl/divinyl copolymerization, we pursued the intramolecular crosslinking reaction to generate the net or loop structure as an origin of CSM, although the locally extensive occurrence of intramolecular crosslinking leads to microgelation. [3,[40][41][42][43][44] Eventually, we reached the preparation of novel loopstructures containing net polymers as the ultimate precursors of CSM consisting of microgel-like NPPs.…”
Section: Molecular Design Of Npps As Modules Of Csm Based On Crosslinmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This ideal NPP formation was developed to the preparation of novel amphiphilic polymers [11] and, moreover, amphiphilic CSMs. [37][38][39] As the latter case of controlling intramolecular crosslinking in the free-radical crosslinking monovinyl/divinyl copolymerization, we pursued the intramolecular crosslinking reaction to generate the net or loop structure as an origin of CSM, although the locally extensive occurrence of intramolecular crosslinking leads to microgelation. [3,[40][41][42][43][44] Eventually, we reached the preparation of novel loopstructures containing net polymers as the ultimate precursors of CSM consisting of microgel-like NPPs.…”
Section: Molecular Design Of Npps As Modules Of Csm Based On Crosslinmentioning
confidence: 99%
“…Thus, we could construct novel CSMs utilizing designed NPPs as modules, providing semi-interpenetrating polymer network (IPN) involving DAT networks and linear poly(BzMA), [46] and simultaneous-IPN between polymethacrylate and polyurethane networks, [47][48][49] novel amphiphilic CSMs [37][38][39]50,51] and patchwork-type CSMs, [52] and so on. Another example is concerned with the emulsion crosslinking (co)polymerization of multivinyl monomers, [53] especially focusing on the formation of reactive crosslinked polymer nanoparticles (CPNs) as models of microgels, with the intention of clarifying the correlation of the network structure with the reactivity of resulting CPNs which would be useful as functionalized polymeric materials.…”
Section: Construction Of Crosslink-systemmaterials Utilizing Designedmentioning
confidence: 99%
“…One reason for the lack of interest is the perceived unlikelihood that kinetic chain length is important in the kinetics of crosslinking systems that quickly form gels of infinite molecular weight. Though it may seem counterintuitive, recent research has shown that chain length does have a measurable effect on the polymerization kinetics of multi‐functional methacrylates . It has been demonstrated that chain length dependent termination is important in crosslinking systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that chain length dependent termination is important in crosslinking systems. Adding a chain transfer agent to the system or increasing the initiation rate (i.e., decreasing the kinetic chain length) leads to a more mobile reaction environment and more rapid termination . Additionally, the presence of a chain transfer agent alters the chemical identity of the radical fragment that begins a polymer chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation